1989
DOI: 10.1111/j.1476-5381.1989.tb11987.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclassification of atrial and intestinal muscarinic receptors of the rat—direct binding studies with agonists and antagonists

Abstract: 1 Although extensively investigated, the extent of differences between receptors mediating negative inotropic and chronotropic responses is still unclear. In the present study atrial and intestinal muscarinic receptors were identified by [3H]-N-methyl-scopolamine ([3H]-NMS) binding and the affinities of some presumably inotropy-or chronotropy-selective agonists and several antagonists determined. 2 All the agonists tested showed similar affinity for right and left atrial receptors. Accepting an affinity differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This suggests that post‐junctional M 2 muscarinic receptors play a role in mediating carbachol‐induced contraction of ileal smooth muscle. Receptor‐binding studies have shown that the majority of muscarinic receptors on ileal smooth muscle are M 2 , with a smaller proportion of M 3 receptors (Brunner, 1989; Lazareno & Roberts, 1989; Kurjak et al ., 1999). Despite the preponderance of M 2 receptors in the ileum, the contractile response to muscarinic agonists is largely due to M 3 receptor activation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that post‐junctional M 2 muscarinic receptors play a role in mediating carbachol‐induced contraction of ileal smooth muscle. Receptor‐binding studies have shown that the majority of muscarinic receptors on ileal smooth muscle are M 2 , with a smaller proportion of M 3 receptors (Brunner, 1989; Lazareno & Roberts, 1989; Kurjak et al ., 1999). Despite the preponderance of M 2 receptors in the ileum, the contractile response to muscarinic agonists is largely due to M 3 receptor activation.…”
Section: Discussionmentioning
confidence: 99%